Tendering process / Muhammad Mawardi Masling - Masling, Muhammad Mawardi (Universiti Teknologi MARA, Perak, 2014)
The successful implementation of a construction project is depends by making the right decision during tendering process. Managing tender procedures is very complex because it is involving coordination of many tasks and individuals with different priorities and objectives. Planning for construction project involving millions ringgit is a challenging and difficult task faced by multiple parties such as clients, consultants and contractors. The construction project involves three stages namely as pre-construction, construction and post-construction. Tendering process is in the first stage as the pre-construction stage. This report is about the procedure of tendering process which involved works of repairing the surface road of "Jalan Lubuk Kiat -Kubang Kuau di KM 3.4 -KM 4.7 (D 181), di KM 5.5 -KM 6.6" and works involved, Pasir Mas, Kelantan. The objective of this report is to discuss about the tendering procedure which is practiced at JKR Pasir Mas. It will focus on the steps and stages of tendering process from advertisement of tender, briefing of the tender, purchase the tender forms and evaluation of the tender. This report also will look at the types of tender that are commonly used in Malaysia Construction Industry. In this report, to obtain information on tendering process, observations and interviews method were used. Observation has been made when briefing of tender is held at JKR Pasir Mas. In addition, by interviewed people who are experienced in the process of tender such as administration assistant, engineers and contractors. Hope that this report can give a lot of advantages and benefits to the reader on how the tender is processed before the construction begins and also can identify the types of tender in Malaysia.